Neurological and Psychological Characteristics of Young Nitrous Oxide Abusers and Its Underlying Causes During the COVID-19 Lockdown - Wu, Gang; Wang, Shanshan; Wang, Tingling; Han, Jiali; Yu, Anna; Feng, Changqiang; Wang, Yajing; Liu, Suzhi (Frontiers in Public Health, 2022)
Background The COVID-19 pandemic has a serious impact on the mental health of the public due to its economic and social impact. And psychological effects have led to drug and alcohol abuse. After the city lifted the lockdown, we consecutively encountered several young nitrous oxide abusers admitted to hospital for neurological treatment. Purpose To inform physician decisions and social intervention, this observational study aimed at investigating the neurological and psychological characteristics of nitrous oxide abusers and its underlying causes during the COVID-19 lockdown. Methods The nitrous oxide abusers who sought neurological treatment at our hospital between May 2020 and June 2020 were enrolled. Clinical data including socio-demographic, physical examination, laboratory examination, electromyography and neuroimaging were collected. Their motivations for inhaling nitrous oxide, knowledge about the nitrous oxide abuse and the accompanying of family were investigated face to face. Psychological status was assessed by the Symptom Checklist 90 (SCL-90) psychological evaluation. Results Six nitrous oxide abusers were enrolled and the age was 22 ± 4.3. Clinical presentations included varying degrees of limb numbness and an ataxic gait. Laboratory examination revealed that all the patients did not have pernicious anemia, 4 patients had decreased vitamin B12 while 3 patients exhibited elevated homocysteine levels. MR of the spinal cord revealed that 4 patients had abnormal signals in the cervical spinal cord of high symmetry with splayed or inverted V sign after T2WI. Electromyogram (EMG) test showed 5 patients had peripheral nerve damage. The SCL-90 psychological evaluation results indicated that all patients had severe anxiety, depression and psychosis and they had severer psychological problems than ordinary citizens. Their motives for inhaling nitrous oxide are to relieve boredom, curiosity and buddy pressure. Their family spent <1 day per week to stay with them during city lockdown. Conclusion The enrolled patients caused by abuse of nitrous oxide presented with symptoms of subacute combined with spinal degeneration. They had more serious psychological problems related to the COVID-19 pandemic. These cases make us value the psychological problems of young people under the outbreak and take multi-layered measures from families, schools (companies), hospitals, and governments to address it.